Death of the TonB Shuttle Hypothesis - Gresock, Michael G.; Savenkova, Marina I.; Larsen, Ray A.; Ollis, Anne A.; Postle, Kathleen (Frontiers in Microbiology, 2011)
A complex of ExbB, ExbD, and TonB transduces cytoplasmic membrane (CM) proton motive force (pmf) to outer membrane (OM) transporters so that large, scarce, and important nutrients can be released into the periplasmic space for subsequent transport across the CM. TonB is the component that interacts with the OM transporters and enables ligand transport, and several mechanical models and a shuttle model explain how TonB might work. In the mechanical models, TonB remains attached to the CM during energy transduction, while in the shuttle model the TonB N terminus leaves the CM to deliver conformationally stored potential energy to OM transporters. Previous efforts to test the shuttle model by anchoring TonB to the CM by fusion to a large globular cytoplasmic protein have been hampered by the proteolytic susceptibility of the fusion constructs. Here we confirm that GFP-TonB, tested in a previous study by another laboratory, again gave rise to full-length TonB and slightly larger potentially “shuttleable” fragments that prevented unambiguous interpretation of the data. Recently, we discovered that a fusion of the Vibrio cholerae ToxR cytoplasmic domain to the N terminus of TonB was proteolytically stable. ToxR-TonB was able to be completely converted into a proteinase K-resistant conformation in response to loss of pmf in spheroplasts and exhibited an ability to form a pmf-dependent formaldehyde crosslink to ExbD, both indicators of its location in the CM. Most importantly, ToxR-TonB had the same relative specific activity as wild-type TonB. Taken together, these results provide the first conclusive evidence that TonB does not shuttle during energy transduction. The interpretations of our previous study, which concluded that TonB shuttled in vivo, were complicated by the fact that the probe used in those studies, Oregon Green® 488 maleimide, was permeant to the CM and could label proteins, including a TonB ∆TMD derivative, confined exclusively to the cytoplasm.